2011
DOI: 10.1016/j.physletb.2011.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Scalaron the mighty: Producing dark matter and baryon asymmetry at reheating

Abstract: In R 2 -inflation scalaron slow roll is responsible for the inflationary stage, while its oscillations reheat the Universe. We find that the same scalaron decays induced by gravity can also provide the dark matter production and leptogenesis. With R 2term and three Majorana fermions added to the Standard Model, we arrive at the phenomenologically complete theory capable of simultaneously explaining neutrino oscillations, inflation, reheating, dark matter and baryon asymmetry of the Universe.Besides the seesaw … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
140
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(152 citation statements)
references
References 31 publications
(60 reference statements)
12
140
0
Order By: Relevance
“…We should mention that the RVM model provides a simple description of the graceful exit and reheating problem; see [23][24][25]27,87] for details. As for the Starobinsky model, the reheating of the Universe after the exit of the inflationary phase has been discussed for example in [88][89][90]. In contrast to the Starobinsky model, a general effective action from where the RVM can be derived is not known [16], and currently, this has been achieved only in some cases [13].…”
Section: Scalar Field Description: Rvm Versus Starobinskymentioning
confidence: 99%
“…We should mention that the RVM model provides a simple description of the graceful exit and reheating problem; see [23][24][25]27,87] for details. As for the Starobinsky model, the reheating of the Universe after the exit of the inflationary phase has been discussed for example in [88][89][90]. In contrast to the Starobinsky model, a general effective action from where the RVM can be derived is not known [16], and currently, this has been achieved only in some cases [13].…”
Section: Scalar Field Description: Rvm Versus Starobinskymentioning
confidence: 99%
“…of [17] and the second Ref. of [39]). If we extend gravitational interaction with matter sector to non-minimal one, preheating can be more efficient even in R 2 inflation [58].…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects of reheating after R 2 inflation have been studied in refs. [16][17][18][19][20][21][22][23]. Ref.…”
Section: Jhep02(2015)105mentioning
confidence: 99%
“…Ref. [19] showed that dark matter and baryon asymmetry are produced at reheating by introducing Majorana neutrinos. Ref.…”
Section: Jhep02(2015)105mentioning
confidence: 99%